2021
DOI: 10.1002/ccd.29585
|View full text |Cite
|
Sign up to set email alerts
|

Thirty‐day and 5‐year results of percutaneous coronary intervention for in‐stent restenotic chronic total occlusion lesions: Data from 2,659 consecutive patients

Abstract: Objectives: To investigate the procedure success rate and clinical outcomes of instent restenotic chronic total occlusion (ISR-CTO) percutaneous coronary intervention (PCI).Background: Few studies have reported the short-and long-term clinical outcomes of ISR-CTO PCI.Method: Patients who underwent ISR-CTO (n = 212) or de-novo CTO (n = 2,447) PCI at Fuwai Hospital from 2010 to 2013 were enrolled. Thirty-day and 5-year clinical outcomes were analyzed. The primary outcome was the incidence of all-cause death, myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The final analysis included 12 studies published between 2011 to 2021, with a total of 708 391 patients: 71 353 patients underwent PCI for ISR, and 637 038 patients underwent PCI for de novo lesions. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 There was good interrater agreement between the 2 researchers performing study selection (κ=0.79; standard error=0.09) and data extraction (κ=0.81; standard error=0.06). The weighted follow‐up duration was 29.8 months.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The final analysis included 12 studies published between 2011 to 2021, with a total of 708 391 patients: 71 353 patients underwent PCI for ISR, and 637 038 patients underwent PCI for de novo lesions. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 There was good interrater agreement between the 2 researchers performing study selection (κ=0.79; standard error=0.09) and data extraction (κ=0.81; standard error=0.06). The weighted follow‐up duration was 29.8 months.…”
Section: Resultsmentioning
confidence: 92%
“…Four of the included studies exclusively evaluated patients with PCI for CTO. 12 , 13 , 16 , 21 PCI with stenting was used in the ISR group in 46% to 49% of patients in 3 studies, 12 , 17 , 20 75% to 89% in 3 studies, 13 , 14 , 16 and 97% to 100% in the remaining studies. Stents used during PCI procedures were exclusively DES in 7 studies, 12 , 16 , 18 , 19 , 20 , 22 , 23 predominantly DES in 3 other studies, 14 , 17 , 21 and in 2 studies the types of stents were not reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison with studies published previously in DES era, the incidence of TVR (11.3%) in our study seemed higher than that demonstrated in a retrospective study including 350 patients with 2-year follow up by Tang G, et al (7.6%), in which 79.4% of de novo CTO lesions were treated by DES [16]. Recently, another retrospective study including 1308 patients with de novo CTO lesion in which 73.9% of patients had stent implantation showed 6.3% TLR and 7.1% TVR in reasonable recanalization subgroup during 5-year follow up [17], which is similar to the 4-year follow up results in the DECISION-CTO trial, the randomized controlled trial (RCT) in CTO PCI [10]. The acute vessel closure, thrombosis after DCB treatment in de novo lesions are major safety concerns of DCBs and the occurrence has been shown to be very low.…”
Section: Discussionmentioning
confidence: 99%